JURIDICAL ANALYSIS OF AUTHORITY OF SEA AND COASTAL GUARDIANS TO REALIZE THE SOVEREIGNTY OF NATIONS AND STATES - Hariyanto, Lilik; Dahlan, Dahlan; Erniyanti, Erniyanti (RADJA PUBLIKA, 2022)
Ensuring the safety and security of shipping in Indonesian waters certainly cannot be separated from the role of the Marine and Coastal Guard Unit in carrying out its functions as a guard and enforcer of laws and regulations at sea and coast, which is the oldest organization in Indonesia that carries out guarding and law enforcement at sea. The history of the Marine and Coastal Guard Unit which began before Indonesia's independence. The problem in this research is how to regulate the legal authority of the Marine and Coast Guard to realize sovereignty, how to implement the authority and what factors are obstacles in exercising the authority to realize the sovereignty of the nation and state. This study uses a descriptive method with the type of normative and sociological research using a normative approach (legal research) to obtain primary data through field research. Shipping in Indonesia refers to Law No. 17 of 2008 and Decree of the Minister of Transportation No. 65 of 2002 concerning the Organization and Work Procedures of Marine and Coast Guard Bases, the authority of the marine and deep coast guarding unit to realize the sovereignty of the nation and state. The conclusion of this study is that the Government as the maker and implementer of laws is expected to make special legislation that discusses the authority of law enforcement agencies at sea to become one door in the prosecution of violations at sea,